Education as a Space for Change: Urban Women’s Experiences of Menstrual Stigma in Kathmandu - Shrestha, Sharmila Chandi (Journal of TESON, 2026)
The study explores lived experiences of menstrual stigma among urban women in Kathmandu, a highly urbanized capital of Nepal. It examines how educational experiences shape their understanding, negotiation and resistance. Drawing on an in-depth qualitative interview with a 22-year-old Bachelor of Education student, the study is theoretically informed by Pierre Bourdieu’s concept of habitus, Ervin Goffman’s theory of stigma and Lev Vygotsky’s social constructivist perspective. Findings reveal that menstrual stigma remains deeply internalized, emotionally experienced and socially enforced through family practices. At the same time, education emerges as a critical space for reflection and agency, enabling women to reinterpret menstruation, negotiate restrictions and engage in gradual forms of resistance. Rather than complete rejection of tradition, findings highlight context-specific and non-linear transformation shaped by both constraint and agency. The study contributes to scholarship on menstruation by highlighting urban women’s experiences and the transformative yet limited role of education in shaping deeply embedded traditional cultural norms.